Identification of OtpR regulated sRNAs in Brucella melitensis expressed under acidic stress and their roles in pathogenesis and metabolism. (February 2017) - Vishnu, Udayakumar S.; Sankarasubramanian, Jagadesan; Gunasekaran, Paramasamy; Rajendhran, Jeyaprakash
Highlights: We identified novel sRNAs expressed in the B. melitensis 16M and 16M ΔotpR under acidic stress. Twelve trans- encoded and 43 cis- encoded sRNAs were differentially expressed 16M ΔotpR . The mRNA targets of these sRNAs were predicted. Functional classification and pathway analysis of mRNA targets revealed that sRNAs are involved in different metabolic pathways. We found sRNAs targeting the major virulence genes in the virB operon. Abstract: Small RNAs (sRNAs) are the small regulatory molecules that regulate various biological processes in bacteria. Though the functions of sRNAs are well documented, very little information is available on the sRNAs of Brucella spp. The otpR is the response regulator of a two-component regulatory system, which plays a significant role in Brucella virulence. In this study, we identified the sRNAs expressed in B. melitensis 16M and its otpR mutant under acidic stress from the RNAseq dataset. We identified 94 trans- encoded and 948 cis- encoded sRNAs in B. melitensis 16M. In B. melitensis 16M ΔotpR under acidic stress 99 trans -encoded and 877 cis- encoded sRNAs were identified. Among these, 12 trans- encoded and 43 cis- encoded sRNAs were upregulated in B. melitensis 16M ΔotpR, with an adjusted P-value ≤ 0.05. The mRNA targets of these sRNAs were predicted. Further, the levels of mRNA targets were examined, and the sRNA-mediated regulatory network was predicted. Functional classification and pathway analysis of mRNA targets provided evidence that sRNAs are involved in different metabolic pathways including carbohydrates, amino acids, lipids, nucleotides transport and metabolism, cell membrane biogenesis and intracellular trafficking of Brucella . We also found that eight transcriptional regulators including a quorum sensing regulator, vjbR are down-regulated by sRNAs. These transcriptional regulators might be responsible for the regulation of several other genes in the otpR mutant. The trans- encoded BsnR88 and cis- encoded BsnR980, BsnR998, BsnR881, BsnR1001, BsnR891, BsnR883, BsnR905 are regulating virB operon genes coding for type IV secretion system (T4SS), which is the major virulence factor of Brucella .